Early mortality in incident hemodialysis patients - A retrospective case-control study - Rita Veríssimo; Luís Leite de Sousa; Tiago J. Carvalho; Pedro Fidalgo (Publicações Ciência e Vida, 2022)
Introduction: Chronic kidney disease has significant morbidity and mortality worldwide. Various studies have demonstrated that incident patients experience a higher mortality rate within the first 3 months of dialysis. Methods: A single-center retrospective case-control study (1:3) was performed to determine early (<90 days) mortality rate and associated risk factors in incident hemodialysis patients from January 2013 to December 2018. We compared variables between survivors and non-survivors at 90 days after initiation of hemodialysis. Multivariate logistic regression was used to calculate the adjusted odds ratio with 95% confidence intervals for the variables associated with early mortality and a predictive model was developed. Results: From a total of 626 incident hemodialysis patients, 48 (7.7%) died before 90 days of treatment. Non-survivors were older [OR 1.07 (1.03-1.11)], had higher rates of non-recovering acute kidney injury [OR 7.91 (3.63- 17.24)], emergency start of hemodialysis [OR 4.31 (2.15-8.62)], congestive heart failure [OR 5.68 (2.81-11.48)], ischemic cardiomyopathy [OR 4.50 (2.25-8.99)], chronic obstructive pulmonary disease [OR 3.60 (1.44-8.95)], Charlson comorbidity index [OR 1.47 (1.27-1.70)] and dependence of assistance in daily living activities [OR 3.46 (1.76-6.82)]. Patients were less likely to have 90-day mortality if they had nephrologist appointments at least 90 days prior to end-stage renal disease [OR 0.25, 95% CI (0.13-0.50); p<0.001] or a higher serum albumin [OR 0.34, 95% CI (0.19-0.62); p<0.001]. Multivariate analysis risk factors independently associated with early mortality were older age [aOR 1.06 (1-01-1.10), p=0.022], acute kidney injury as cause of end-stage renal disease [aOR 12.62 (4.50-35.40), p<0.001], congestive heart failure [aOR 3.79 (1.58-9.11), p=0.003], and Charlson comorbidity index [aOR 1.30 (1.09-1.56), p=0.005]. The model showed very good discriminative ability [AUROC (95% CI) 0.88 (0.83-0.94)]. Conclusion: Early mortality occurred in 7.7% of our population. Our model could be used to identify patients at higher risk of death during the first 90 days of hemodialysis and aid informed decision-making regarding end-stage renal disease treatment options.